Mechanism of substrate recognition and release of human SGLT2 - Wenhao Cui; Zejian Sun; Jiaxuan Xu; Xiaoyu Liu; Yunlu Kang; Lei Chen (Nature Communications)
Abstract Glucose is a vital energy source essential for life and human health. Sodium-glucose cotransporter 2 (SGLT2) is a sodium-glucose symporter that utilizes the electrochemical gradient of sodium to reabsorb glucose from kidney filtrate back into circulation. SGLT2 plays a crucial role in maintaining blood glucose homeostasis and is an important drug target for type 2 diabetes. Despite its significance, the mechanisms by which SGLT2 recognizes and releases substrates during its transport cycle remain largely unknown. Here, we present structures of human SGLT2 in complex with a glucose analogue in the occluded conformation at 2.6 Å resolution, revealing a detailed hydrogen bonding network at the substrate binding site that governs substrate recognition. Additionally, structures of SGLT2 in both the substrate-bound inward-facing conformation and the substrate-free inward-facing conformations illustrate the structural changes that occur during substrate release into cytosol. Our structural analysis, combined with mutagenesis results, identifies specific polar interactions that are essential for maintaining the outer and inner gates in their closed conformations.